Graphene/TiO2-Ag Based Composites Used as Sensitive Electrode Materials for Amaranth Electrochemical Detection and Degradation. Issue 8 (1st January 2018) - Pogacean, Florina; Rosu, Marcela-Corina; Coros, Maria; Magerusan, Lidia; Moldovan, Marioara; Sarosi, Codruta; Porav, Alin-Sebastian; Staden, Raluca-Ioana Stefan-van; Pruneanu, Stela
Abstract : Graphene/TiO2 -Ag based composites having various quantities of TiO2 -Ag nanoparticles (5, 10 or 15 wt%) were successfully prepared through a facile chemical-thermal route. The morphological and structural characteristics of the synthesized materials denoted GTA-5, GTA-10 and GTA-15 were investigated by TEM, XRD and FTIR techniques. The composites were used for the modification of three gold electrodes (Au/GTA-5, Au/GTA-10, Au/GTA-15) which were next employed in the electrochemical detection and degradation of amaranth (an azo dye model). The electrode with the best performance in terms of sensitivity was the Au/GTA-10 electrode. It had considerably larger sensitivity (24 mA/M), in comparison with that of Au/GTA-5 and Au/GTA-15 electrode (8 mA/M and 12 mA/M, respectively). The limit of detection was the same for all modified electrodes (LOD = 1 × 10 −7  M; S/N = 3). The Au/GTA-10 electrode was also tested at the electrochemical degradation of amaranth, from aqueous solutions. The degradation reaction followed a first order kinetics with a half-time of degradation of 203 minutes. The response characteristics of the proposed sensor made it a good candidate for integration in the Ubiquitous sensor's network for IOT.